A brief overview of BNIP3L/NIX receptor‐mediated mitophagy. Issue 12 (11th October 2021) - Marinković, Mija; Novak, Ivana
Abstract : Mitophagy is a form of autophagy specialized to selectively remove mitochondria. Although the PINK1/Parkin pathway is the best described mitophagy of damaged mitochondria, receptor/mediated mitophagy seems to have a pivotal role in cellular development and specialization. The most studied mitophagy receptor BCL2/adenovirus E1B 19‐kDa‐interacting protein 3‐like (BNIP3L/NIX) is shown to be important for the programmed removal of healthy mitochondria during terminal differentiation of erythrocytes, but its role has been proven in various cell types. Despite recent advances in our understanding of its regulation by phosphorylation and dimerization, there remain numerous questions on how BNIP3L/NIX tightly balances between cellular life and death decisions. This brief review intends to summarize ongoing dilemmas related to BNIP3L/NIX. Abstract : The inactive form of the BCL2/adenovirus E1B 19‐kDa‐interacting protein 3‐like (BNIP3L/NIX) receptor is found as a monomer phosphorylated on C‐terminal serine 212. Upon mitophagy induction, the receptor is dephosphorylated and this allows BNIP3L/NIX monomers to form the active form of the receptor, BNIP3L/NIX dimer, which is also additionally activated with double phosphorylation near the LIR domain. Dimerization enables stronger recruitment of autophagosomes on selected mitochondria and more efficient mitophagy.